The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/ico.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Clinical Characteristics of Patients With Herpes Simplex and Varicella Zoster Keratitis, Presenting to a New Zealand Emergency Eye Clinic

Abstract: Patients with asthma, CVD, on long-term corticosteroid inhalers or creams, or of Maori ethnicity need particular assessment to investigate herpes simplex as a possible cause of keratitis. Clinicians prescribing inhaled corticosteroids or topical corticosteroid creams should be aware of possible association with herpes simplex keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Among studies that examined the effect of patient characteristics on outcome, neither age nor gender influenced the rate of corneal healing during antiviral therapy for HSV epithelial keratitis (de Koning 1982; de Koning 1983; Jackson 1984; McCulley 1982; van Bijsterveld 1980; van Bijsterveld 1989). Observational studies have suggested that some ethnic groups may be susceptible to recurrent HSV epithelial keratitis (McDonald 2015; Wilhelmus 1996a), but ethnicity was not significantly associated with recurrence in a cohort followed for 18 months (HEDS Group 2001). Insufficient information was available to examine age, gender, or ethnicity as possible effect modifiers in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies that examined the effect of patient characteristics on outcome, neither age nor gender influenced the rate of corneal healing during antiviral therapy for HSV epithelial keratitis (de Koning 1982; de Koning 1983; Jackson 1984; McCulley 1982; van Bijsterveld 1980; van Bijsterveld 1989). Observational studies have suggested that some ethnic groups may be susceptible to recurrent HSV epithelial keratitis (McDonald 2015; Wilhelmus 1996a), but ethnicity was not significantly associated with recurrence in a cohort followed for 18 months (HEDS Group 2001). Insufficient information was available to examine age, gender, or ethnicity as possible effect modifiers in this review.…”
Section: Discussionmentioning
confidence: 99%
“…• Intravitreal corticosteroid (Gulkilik 2007;Shtein 2007) Other immunosuppressive treatment • Topical ophthalmic calcineurin inhibitor (Field 1995;Joseph 2005) • Inhaled corticosteroid (Garcia-Medina 2011;McDonald 2015) • Systemic immunosuppressants following organ or bone marrow transplantation (Hayashi 2008;Kremer 1991;Ng 1998) • Systemic immunosuppressants given for autoimmune disorders (Larrañaga Fragoso 2015)…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In particular, HZ ophthalmicus (HZO) arising from the ophthalmic division accounts for 5% to 25% of HZ cases in Asia-Pacific countries [11, 15, 17, 22, 30, 102, 104, 136, 154, 340, 354] (Table 5). The majority of cases, especially those accompanied by nose eruptions (Hutchinson's sign) [372–375], are complicated by secondary inflammation such as conjunctivitis, keratitis [376–378], scleritis, and uveitis/iridocyclitis [372–374, 379–381]. Such complications can cause glaucoma and are potentially blinding, especially if not treated promptly [379, 382].…”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…M aori are overrepresented in herpes simplex keratitis, accounting for an estimated 22% of cases in the Auckland region. 50 Of the total presumed microbial keratitis cases among M aori, herpes simplex accounts for a significant proportion (71%). The diagnosis of herpes simplex keratitis increases almost fivefold among M aori compared to non-M aori.…”
Section: Herpes Simplex Keratitis and Varicella Zoster Keratitismentioning
confidence: 99%